Family Support and Quality of Life in Breast Cancer Patients - Noorhidayah Noorhidayah; Hesti Prawita Widiastuti; Umi Kalsum (Humanistic Network for Science and Technology (HNST), 2020)
Introduction: In these days, one of the terrifying cancers for women throughout the world is breast cancer. The treatment of cancer should be holistic. Patients need family support to create a good quality of life. The purpose of this study was to determine the relationship between family support and quality of life in breast cancer patients at the Chemotherapy Unit of Abdul Wahab Sjahranie Hospital Samarinda. Methods: Quantitative research with analytical study and cross-sectional design. Sampling was done with a total sample of 76 respondents. The instruments used in this research were family support standards and the Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) for quality of life. The data were analyzed using the Chi-Square test. Results: The p-value was 0.003, OR = 4.090, indicating that there was a relationship between family support and quality of life in breast cancer patients. Conclusion: There is a relationship between family support and quality of life in breast cancer patients. It is expected that the hospital can proceed in providing health education and motivation to breast cancer patients and their families related to the importance of family support for the quality of life of breast cancer patients. Keywords: family support; breast cancer; quality of life